2018
DOI: 10.3390/mi9080413
|View full text |Cite
|
Sign up to set email alerts
|

Wide Acoustic Bandgap Solid Disk-Shaped Phononic Crystal Anchoring Boundaries for Enhancing Quality Factor in AlN-on-Si MEMS Resonators

Abstract: This paper demonstrates the four fold enhancement in quality factor (Q) of a very high frequency (VHF) band piezoelectric Aluminum Nitride (AlN) on Silicon (Si) Lamb mode resonator by applying a unique wide acoustic bandgap (ABG) phononic crystal (PnC) at the anchoring boundaries of the resonator. The PnC unit cell topology, based on a solid disk, is characterized by a wide ABG of 120 MHz around a center frequency of 144.7 MHz from the experiments. The resulting wide ABG described in this work allows for great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Among them, it is shown by Ardito et al [ 103 ] that solid-disk PnC unit cell outperforms others in that is has larger band gap width, which is believed to help confine the acoustic waves. Recently, Siddiqi et al [ 104 ] demonstrated this concept in a 141-MHz AlN-on-Si LVR as shown in Figure 7 e. In this work, the solid-disk PnC is characterized by a wide bandgap of 120 MHz around a center frequency of 144.7 MHz. The measured enhancement in Q is 4.2 times to realize Qs of about 10,000, which is significantly higher than previous works, as shown in Figure 7 d. This greater Q enhancement confirms that wider bandgap of PnCs helps reduce anchor loss in LVRs.…”
Section: Q-enhancement Strategies For Lvrsmentioning
confidence: 70%
See 2 more Smart Citations
“…Among them, it is shown by Ardito et al [ 103 ] that solid-disk PnC unit cell outperforms others in that is has larger band gap width, which is believed to help confine the acoustic waves. Recently, Siddiqi et al [ 104 ] demonstrated this concept in a 141-MHz AlN-on-Si LVR as shown in Figure 7 e. In this work, the solid-disk PnC is characterized by a wide bandgap of 120 MHz around a center frequency of 144.7 MHz. The measured enhancement in Q is 4.2 times to realize Qs of about 10,000, which is significantly higher than previous works, as shown in Figure 7 d. This greater Q enhancement confirms that wider bandgap of PnCs helps reduce anchor loss in LVRs.…”
Section: Q-enhancement Strategies For Lvrsmentioning
confidence: 70%
“…However, building the delicate structures required for the acoustic reflector on tethers usually compromise the robustness of the mechanical support, making it vulnerable to mechanical shock. Among these strategies based on acoustic reflectors, PnCs have been extensively researched during the past decade [ 97 , 100 , 104 , 105 ]. The obvious advantage of using PnCs as acoustic reflectors is that it usually offers a frequency stopband that prevents the propagation of elastic wave in any type (i.e., longitudinal or shear wave).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the tuning range, frequency stability, and quality factor (Q) of micro-resonators are the focus in References [5,6,7] correspondingly, all of which are of significant practical importance, specifically in oscillator applications. The authors of [5] propose two methods for extending tuning range through stiffness alteration that could be effectively implemented in torsional resonators.…”
mentioning
confidence: 99%
“…In Reference [6], frequency stability in response to applied acceleration is investigated in bulk-extensional single crystalline silicon resonators and the dependency of acceleration-sensitivity on the resonator orientation with respect to the silicon crystalline planes are studied through finite element modeling and demonstrated through measurement. In Reference [7], the authors present the effectiveness of phononic crystal band-gap structures in improving the Q in bulk-extensional micro-resonators by reflecting acoustic energy back to the acoustic cavity, as they are strategically placed outside the anchors.…”
mentioning
confidence: 99%